Analysis of root traits of watermelon under phosphate fertilization using minirhizotrons (Research, Society and Development, 2020)
The objective of the present study was to assess the effects of phosphate fertilization management on root traits of irrigated watermelon crop by minirhizotron observation. The experiment was conducted in an area with acrisol soil in Mossoró-RN using a completely randomized block design with six replicates corresponding to the assessment times. The evaluated parameters were four doses of P (34, 80, 137, and 206 kg ha−1 de P2O5) and two methods of fertilization: basal fertilization (F0) and basal + top-dressing fertilization (F1). Triple superphosphate was used for basal fertilization and monoammonium phosphate was used for top-dressing (34 kg ha−1 of P2O5). In addition, two control treatments were included: one without the use of P (C1) and another with only top-dressed P at a dose of 103 kg ha−1 of P2O5 (C2). A portable root scanner was used to collect images through 0.6-m clear tubes (minirhizotrons). The root mean diameter decreased with increasing doses of phosphate in F0; however, fine roots were observed in C2. There was a positive effect of P doses on the number of roots only in F0. In the absence of P, the reduction in the number of roots was greater than the reduction in total length.